Pengaruh Kepuasan, Kepercayaan, Dan Pengalaman Konsumen Terhadap Loyalitas Bedak Muka Pixy Di Kota Batam - Indah Amelia Cahyani; Hikmah, Hikmah (SCIENTIA JOURNAL, 2025)
Increasingly tight business competition requires companies to implement effective marketing strategies to maintain consumer loyalty. This study aims to evaluate the effect of consumer satisfaction, trust, and experience on the loyalty of Pixy face powder users in Batam City. A quantitative descriptive approach was used in this study involving 204 respondents selected through purposive sampling techniques based on the Jacob Cohen formula. The data analysis process includes data quality testing, classical assumption testing, influence testing, and hypothesis testing. The results of the t-test indicate that satisfaction has a positive and partially significant effect on loyalty, trust has a positive and partially significant effect on loyalty, and consumer experience also contributes positively and partially significantly to loyalty. The findings are also reinforced by the results of the F test which indicate that simultaneously, the variables of satisfaction, trust, and consumer experience show a positive and significant effect on loyalty. These findings underline the importance of increasing consumer satisfaction, trust, and experience to maintain the loyalty of Pixy face powder users in Batam City.